The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1371/journal.pone.0024721
|View full text |Cite
|
Sign up to set email alerts
|

HBV Infection in Relation to Consistent Condom Use: A Population-Based Study in Peru

Abstract: BackgroundData on hepatitis B virus (HBV) prevalence are limited in developing countries. There is also limited information of consistent condom use efficacy for reducing HBV transmission at the population level. The study goal was to evaluate the prevalence and factors associated with HBV infection in Peru, and the relationship between anti-HBc positivity and consistent condom use.Methods and FindingsData from two different surveys performed in 28 mid-sized Peruvian cities were analyzed. Participants aged 18–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…This finding is in consensus with researches of the past which Identified sharing of needles/syringes and personal care items, direct contact with blood and sores, and unprotected sex as rick factors for the contraction of Hepatitis B, and vaccination as the mainstay of the infection [2,5,14,15]. According to WHO [2], the Hepatitis B vaccine as effectively prevented HBV infection since 1982, that perhaps the reason why [16] emphasized the need for prevention programs (vaccination) and imply that condom use promotion could be a potential strategy to prevent HBV infection and other sexually transmitted pathogens. teachers obtain their information about Hepatitis B.…”
Section: Discussionsupporting
confidence: 81%
“…This finding is in consensus with researches of the past which Identified sharing of needles/syringes and personal care items, direct contact with blood and sores, and unprotected sex as rick factors for the contraction of Hepatitis B, and vaccination as the mainstay of the infection [2,5,14,15]. According to WHO [2], the Hepatitis B vaccine as effectively prevented HBV infection since 1982, that perhaps the reason why [16] emphasized the need for prevention programs (vaccination) and imply that condom use promotion could be a potential strategy to prevent HBV infection and other sexually transmitted pathogens. teachers obtain their information about Hepatitis B.…”
Section: Discussionsupporting
confidence: 81%
“…As expected, PW who used condoms were less likely to be HBV-infected compared to those who never used condoms. This finding indicates that, in addition to vaccination programs to prevent HBV infection among PW, education regarding condoms could be another means of protecting PW from STIs [45]. PW with multiple partners and who reported STIs in the past were also more likely to be HBV-infected.…”
Section: Discussionmentioning
confidence: 91%
“…The reason for this finding is not clear as it has been severally reported that condom use protects against sexually transmitted diseases including HBV. 47,48 However the respondents' knowledge of proper condom use was not sought for in this study.…”
Section: Agementioning
confidence: 99%